Peningkatan Kualitas Fasilitas Wisata Di Schmutzer Ragunan Sebagai Upaya Untuk Meningkatkan Kepuasan Pengunjung - Jerubun, Emanuel; Nugraha, Rizki Nurul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to outline strategies to improve the guality of facilities in tourist destinations Schmutzer Ragunan to increase visitor satisfaction. Schmutzer Ragunan is a populer destination in Ragunan that offers interesting facilities and attractions. The research involved travel experts, Schmutzer management and related parties. Collaboratively, they identify facility problems and plan upgrades accordingly. Specific time-bound research, including problem analysis, planning, implemementation, andevalution. This study aims to improve visitor satisfactions at Schmutzer Ragunan by improving facilities. This is expected to increase repeat visits and positive recommendations. The focus is on the quality of facilities in those destinations, areas that need improvement. The approach involves guestionnaires, facility observation and management. The approach involves guestionnaires, facility observation and management interviews. Data is analyzed to identify visitor needs, problems, and opportunities. Improvement strategies and recommendations are drawn up.